PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA MOTOR KAWASAKI PRIMA DI KOTA BATAM - KURNIA SARI; JONTRO SIMANJUNTAK (JURNAL ILMIAH KOHESI, 2020)
This study aims to determine the effect of service quality and promotion on motorcycle purchasing decisions in KawasakiPrima Batam. This research design is a type of quantitative research using a causal associative approach. The results of thestudy based on the t-test for service quality have a value of 3,217 > 1.65622 and a significance of 0.002 < 0.05 which meansthat the service quality variable has a positive and significant effect on purchasing decision variables, while the t test forpromotion has a value of 4.962> 1.65622 and is significant .000 < 0.05 which means promotion has a positive and significantinfluence on purchasing decisions. F test results of 19,707 > 3,94 with a significance value of .000 < 0.05, it can be concludedthat the quality of service and promotion together have a significant influence on purchasing decisions.